The costs of favoritism: Is politically-driven aid less effective? - Axel Dreher; Stephan Klasen; James Raymond; Eric Werker (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2010)
As is now well documented, aid is given for both political as well as economic reasons. The conventional wisdom is that politically-motivated aid is less effective in promoting developmental objectives. We examine the ex-post performance ratings of World Bank projects and generally find that projects that are potentially politically motivated - such as those granted to governments holding a non-permanent seat on the United Nations Security Council or an Executive Directorship at the World Bank - are no more likely, on average, to get a negative quality rating than other projects. When aid is given to Security Council members with higher short-term debt, however, a negative quality rating is more likely. So we find evidence that World Bank project quality suffers as a consequence of political influence only when the recipient country is economically vulnerable in the first place.
Keywords: O19; O11; F35; 330; World Bank; Aid Effectiveness; Political Influence; United Nations Security Council; Entwicklungshilfe; Entwicklungsfinanzierung; Entwicklungsprojekt; Projektbewertung; Public Choice; Internationale Organisation; Internationale Sicherheit; Mitgliedschaft; Auslandsverschuldung; Welt